Bio-guided fractionation and isolation of active component from Tragopogon graminifolius based on its wound healing property. (15th November 2018) - Bayrami, Zahra; Hajiaghaee, Reza; Khalighi-Sigaroodi, Farahnaz; Rahimi, Roja; Farzaei, Mohammad Hosein; Hodjat, Mahshid; Baeeri, Maryam; Rahimifard, Mahban; Navaei-Nigjeh, Mona; Abdollahi, Mohammad
Abstract: Ethnopharmacological relevance: Tragopogon graminifolius ( T. graminifolius ) from Asteraceae family has been used as a remedy in Persian traditional medicine for the treatment of various disorders such as wound healing. Aim of the study: The purpose of this study is to investigate the compounds of T. graminifolius, which are responsible for its wound healing activity. Materials and methods: The experiment was performed in three phases; each phase consisted of fractionation of extracts followed by scratch assay. The results of the scratch assay were expressed using scratch closure index (SCI), representing the contraction of scratch. Results: In phase I, Ethyl acetate fraction (E) showed the maximum SCI (61.7 ± 3.5) that was selected for more fractionation in the next phase. In phase II, 12 fractions were obtained and labeled as fractions E- A to L, respectively. Based on the SCI of fractions, EF (SCI=68.9 ± 0.6) was the most active fraction in phase II and selected for further fractionation in phase III. In phase III, 8 fractions were resulted by fractionation of EF and labeled as EF- 1–8. Fraction EF5 with the highest SCI (30.8 ± 3.0) was the most effective fraction and Luteolin was the main component. Luteolin significantly improved viability of fibroblast cells and increased cell population that was accompanied by decreased cell apoptosis. Luteolin-induced cell number increase in the S and G2M phases of the cell cycle, further confirms the proliferative effect of this compound. Conclusion: The results showed that the total extract and fractions of T. graminifolius stimulate proliferation and migration of skin fibroblast cells and Luteolin is one of the active compounds responsible for these effects. Graphical abstract: